Negative active material, negative electrode composition, negative electrode comprising the same, and secondary battery

By applying a coating to silicon-based active materials, which includes metal oxides and aqueous binders, the problems of volume expansion and particle breakage of silicon-based active materials in lithium secondary batteries are solved, improving the capacity retention and stability of the battery, reducing gas generation, and improving the electrode manufacturing process.

CN123057601APending Publication Date: 2026-11-06LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580024825.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-10-22
Filing Date
2025-10-20
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

In existing lithium secondary batteries, when silicon-based active materials are used as negative electrode active materials, there are problems of volume expansion and particle breakage, resulting in poor capacity retention and stability, and undesirable gases are easily generated during processing.

Method used

A coating is applied to the silicon-based active material, comprising metal oxides and aqueous binders, to improve the capacity retention and stability of the battery, suppress particle expansion and breakage, and reduce gas generation during processing.

Benefits of technology

By applying a coating, the expansion and breakage of silicon-based active materials are reduced, improving the battery's capacity retention and stability, suppressing gas generation, and enhancing the electrode manufacturing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123057601A_ABST
    Figure CN123057601A_ABST
Patent Text Reader

Abstract

The present application relates to a negative electrode active material, a negative electrode composition, a negative electrode comprising the same, a secondary battery comprising the negative electrode, a battery module, and a battery pack. The negative electrode active material according to one embodiment of the present application comprises a silicon-based active material and a coating layer provided on the silicon-based active material, wherein the coating layer comprises a metal oxide and a water-based binder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application is based on and claims priority to Korean Patent Application No. 10-2024-0145317, filed on October 22, 2024, with the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety.

[0002] This disclosure relates to negative electrode active materials, negative electrode compositions, negative electrodes comprising the same, secondary batteries comprising the negative electrodes, battery modules, and battery packs. Background Technology

[0003] The rapid increase in fossil fuel use has led to a growing demand for alternative or clean energy sources. In response to this demand, one of the most active research areas is the generation and storage of electricity using electrochemical reactions. Currently, a representative example of electrochemical devices utilizing this electrochemical energy is the secondary battery, and its applications are gradually expanding.

[0004] On the other hand, with the technological advancements and increasing demands of mobile devices, the demand for rechargeable batteries is also rapidly increasing. Among rechargeable batteries, lithium-ion batteries, characterized by high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used. Furthermore, in order to manufacture electrodes for high-capacity lithium-ion batteries, research is actively underway to develop high-density electrodes with even higher energy density per unit volume. Summary of the Invention

[0005] Technical issues

[0006] This disclosure provides a technique for improving the capacity retention and stability of a battery through surface treatment, in which a coating is applied to a silicon-based active material.

[0007] Technical means

[0008] In one embodiment of this disclosure, the negative electrode active material comprises a silicon-based active material and a coating disposed on the silicon-based active material, wherein the coating comprises a metal oxide and a water-based binder.

[0009] In another embodiment, the negative electrode composition comprises a negative electrode active material according to the present disclosure.

[0010] In another embodiment, the negative electrode comprises a negative electrode current collector layer and a negative electrode active material layer disposed on one or both surfaces of the negative electrode current collector layer, wherein the negative electrode active material layer comprises a negative electrode composition according to the present disclosure.

[0011] In another embodiment, the secondary battery includes a positive electrode and a negative electrode according to the present disclosure.

[0012] In another embodiment, the battery module or battery pack includes a secondary battery according to the present disclosure.

[0013] In another embodiment, the battery pack includes a battery module according to the present disclosure.

[0014] Technical effect

[0015] In one embodiment of this disclosure, the negative electrode active material comprises silicon particles and a coating disposed on the silicon particles, the coating comprising a metal oxide and a water-based binder.

[0016] In one embodiment of this disclosure, by providing a coating on the surface treatment of the silicon-based active material, the negative electrode active material can reduce the exposed surface caused by particle expansion and particle breakage of the silicon-based active material under battery operating conditions, thereby improving the battery's capacity retention and stability.

[0017] For example, the coating can be used as a resist agent for the silicon-based active material to mitigate particle breakage.

[0018] Furthermore, when the negative electrode active material according to one embodiment of the present disclosure is applied, gas generation in aqueous processes can be suppressed, thereby facilitating electrode manufacturing. Attached Figure Description

[0019] The following figures illustrate embodiments of this disclosure and, together with the detailed description of this disclosure that follows, are used to further understand the technical ideas of this disclosure. Therefore, this disclosure should not be construed as limited to the matters shown in the figures.

[0020] Figure 1 A negative electrode active material according to one embodiment of the present disclosure is shown.

[0021] Figure 2 A stacked structure of the negative electrode according to one embodiment of the present disclosure is shown.

[0022] Figure 3 A stacked structure of a secondary battery according to one embodiment of the present disclosure is shown.

[0023] In the various figures of the accompanying drawings, corresponding reference numerals indicate corresponding constituent elements. The figures are presented for simplicity and clarity and are not necessarily drawn to scale. For example, the dimensions of some elements in the figures may be enlarged relative to other elements to aid in understanding the various embodiments. Furthermore, common but well-known elements that are useful or necessary in commercially viable embodiments are generally not depicted so as not to obstruct observation of these various embodiments. Detailed Implementation

[0024] Before describing the contents of this disclosure, let’s first define some terms.

[0025] Throughout this specification, unless otherwise specifically stated, when a part is said to "contain" a constituent element, this does not exclude other constituent elements, but rather includes them.

[0026] As used in this article, "p to q" refers to the range above p and below q.

[0027] As used herein, "specific surface area" is measured by the Brunauer-Emmett-Teller (BET) method, for example using a BELSORP-mini II manufactured by BEL Japan, calculated from the amount of nitrogen adsorbed at liquid nitrogen temperature (77K). For example, in this disclosure, BET specific surface area may refer to the specific surface area measured by the aforementioned method. BET specific surface area can be measured using N2 according to DIN 66131.

[0028] As used herein, “Dn” denotes particle size distribution and refers to the particle size at the n% point of the cumulative particle number distribution according to particle size. For example, D50 is the particle size (median particle size) at the 50% point of the cumulative particle number distribution according to particle size, D90 is the particle size at the 90% point of the cumulative particle number distribution according to particle size, and D10 is the particle size at the 10% point of the cumulative particle number distribution according to particle size. Alternatively, the median particle size can be measured using laser diffraction. For example, the powder to be measured is dispersed in a dispersion medium and introduced into a commercially available laser diffraction particle size measurement device (e.g., Microtrac S3500) to measure the difference in diffraction pattern according to particle size as the particles pass through the laser beam, thereby calculating the particle size distribution.

[0029] As used in this article, particle size or particle diameter can refer to the average or representative diameter of the individual particles that form the particulate powder.

[0030] As used herein, the term "particle size" can refer to the average or representative diameter of a particle. The particle can be in the form of a single particle or a secondary particle in which multiple primary particles are aggregated. Additionally, the median particle size can be used in the same sense as the average particle size, D50, or particle size, and the median particle size can represent the size of the particle.

[0031] As used in this article, the term "particle" can refer to a single particle, a quasi-single particle, or a secondary particle.

[0032] As used herein, the term "single particle" can refer to a single primary particle and can include quasi-single particles formed by the aggregation, bonding, or assembly of up to 30 primary particles.

[0033] As used in this article, the term "secondary particle" refers to a particle formed by the aggregation, bonding, or assembly of dozens to hundreds of primary particles, such as more than 30 primary particles.

[0034] In this specification, when a polymer contains a monomer as a monomeric unit, it means that the monomer participates in the polymerization reaction and is included in the polymer as a repeating unit. In this specification, when a polymer is described as containing a monomer, it should be interpreted in the same way as a polymer containing a monomer as a monomeric unit.

[0035] As used herein, unless specified as “homogeneous polymer,” the term “polymer” is understood to be used in a broad sense that includes copolymers.

[0036] In this specification, weight-average molecular weight (Mw) and number-average molecular weight (Mn) are converted molecular weights of polystyrene measured by gel permeation chromatography (GPC) using commercially available monodisperse polystyrene polymers of various degrees of polymerization (standard samples) as standard materials for molecular weight measurement. Unless otherwise stated, molecular weight in this specification refers to weight-average molecular weight.

[0037] As used herein, the terms “about,” “approximately,” and “substantially” refer to a range or approximation of a value or degree that takes into account inherent manufacturing and material tolerances (e.g., ±5%).

[0038] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode contains a negative electrode active material that intercalates and releases lithium ions from the positive electrode, and silicon particles with a large discharge capacity can be used as the negative electrode active material.

[0039] In response to the recent increase in demand for high-energy-density batteries, efforts have been made to utilize materials such as Si / C or SiO, which have higher capacity compared to graphite-based materials. x Methods for increasing capacity using silicon-based compounds as negative electrode active materials have been extensively studied. Compared to conventionally used graphite, silicon-based compounds, as high-capacity materials, have the advantage of greater capacity. However, these silicon-based compounds undergo rapid volume expansion during charging, which disrupts the conductive path and degrades battery characteristics. For example, Japanese Patent Application Publication No. 2009-080971 discloses the use of polyacrylate as a binder in a graphite-based negative electrode active material layer.

[0040] Therefore, various methods have been proposed to address the issues associated with using silicon-based active materials as anode active materials, such as adjusting the operating potential, additionally coating a thin film on the surface of the active material layer, controlling the content of the silicon-based active material within the anode, suppressing volume expansion itself, or preventing interruption of the conductive path. However, these methods may actually reduce battery performance, thus limiting their application and restricting the commercialization of anodes containing high levels of silicon-based compounds.

[0041] In view of these circumstances, this disclosure provides a technique for improving the capacity retention and stability of lithium secondary batteries through surface treatment, in which a coating is applied to a silicon-based active material used as a negative electrode active material.

[0042] The following describes in detail embodiments of this disclosure to enable those skilled in the art to readily implement it. However, this disclosure can be implemented in various different forms and is not limited to those described below.

[0043] Recently, efforts have been made to increase capacity by applying silicon-based active materials to the anode. However, when silicon-based active materials are used as anode active materials, problems such as volume expansion and gas generation during processing have occurred, resulting in anodes containing silicon-based active materials exhibiting poor performance in terms of capacity retention and stability.

[0044] Negative electrode active materials

[0045] In one embodiment of this disclosure, the negative electrode active material comprises a silicon-based active material and a coating disposed on the silicon-based active material, wherein the coating comprises a metal oxide and a water-based binder.

[0046] By applying the coating comprising metal oxide and aqueous binder to the silicon-based active material, surface exposure caused by particle expansion and rupture of the silicon-based active material is reduced, improving the capacity retention and stability of the battery, and suppressing the generation of undesirable gases during processing.

[0047] In one embodiment of this disclosure, the silicon-based active material may have an average particle size (D50) of about 1 μm to 20 μm. For example, the average particle size (D50) of the silicon-based active material may be more than about 1 μm, greater than 1 μm, more than 2 μm, or more than 3 μm, and may be less than 20 μm, less than 15 μm, less than 14 μm, less than 13 μm, or less than 10 μm.

[0048] In one embodiment of this disclosure, the silicon-based active material typically has a characteristic BET specific surface area. The BET specific surface area of ​​the silicon-based active material is approximately 0.01 m².2 / g to 150m 2 / g, about 0.1m 2 / g to 100m 2 / g, about 0.2m 2 / g to 80m 2 / g or 0.2m 2 / g to 18m 2 / g. The BET specific surface area is measured according to DIN 66131 (using nitrogen).

[0049] In one embodiment of the present disclosure, the silicon-based active material comprises at least one selected from Si, SiO x (0<x<2), Si / C and Si alloys.

[0050] In one embodiment of the present disclosure, when the silicon-based active material comprises Si, the Si is present in an amount of about 70 parts by weight or more, based on 100 parts by weight of the silicon-based active material. For example, based on 100 parts by weight of the silicon-based active material, the Si may be present in an amount of about 70 parts by weight or more, 80 parts by weight or more, 90 parts by weight or more, or 95 parts by weight or more, and may be about 100 parts by weight or less, less than 100 parts by weight, 99 parts by weight or less, 97 parts by weight or less, or 95 parts by weight or less.

[0051] In the present disclosure, the Si refers to pure silicon (Si) particles. For example, using pure silicon (Si) particles as the silicon-based active material may mean that the content of pure Si particles not combined with other particles or elements (SiO x (x=0)) is within the above range, based on 100 parts by weight of the total silicon-based active material.

[0052] In one embodiment of the present disclosure, based on 100 parts by weight of the negative electrode active material, the silicon-based active material may be formed of silicon-based particles having 100 parts by weight of Si, and the silicon-based particles may be in the form of powder.

[0053] In one embodiment of the present disclosure, the silicon-based active material may comprise metal impurities. In this case, the impurities may be metals that can be conventionally contained in the silicon-based active material, and the content of the impurities may be, for example, about 0.1 parts by weight or less, based on 100 parts by weight of the silicon-based active material.

[0054] In one embodiment of the present disclosure, the silicon-based active material may comprise Si / C.

[0055] In this disclosure, Si / C refers to a silicon-carbon composite. The silicon-carbon composite can be formed from unbonded Si and C atoms, but may additionally include other components as needed. For example, the silicon-carbon composite may or may not contain silicon carbide (SiC). When the silicon-carbon composite contains silicon carbide, the silicon carbide content is about 3% by weight or less. The silicon-carbon composite can exist in a crystalline, amorphous, or mixed state. In one example, the C in the silicon-carbon composite may be in an amorphous state.

[0056] The silicon-carbon composite can be formed by combining silicon and carbon, and can form a structure in which a core obtained by combining silicon and carbon is surrounded by graphite, graphene, or amorphous carbon. In the silicon-carbon composite, the silicon can be nano-silicon.

[0057] The silicon-carbon composite can be formed by physically or chemically combining carbon and silicon materials, and there are no restrictions on this, as long as the carbon and silicon materials constitute a composite.

[0058] According to one embodiment of this disclosure, the Si / C may comprise porous carbon and silicon deposited on the porous carbon. For example, the silicon-carbon composite comprises porous carbon particles and silicon particles disposed on the surface of the porous carbon particles or in the pores within the porous carbon particles.

[0059] The silicon particles formed on the surface and in the internal pores of the carbon particles can be silicon nanoparticles, and the silicon nanoparticles can be crystalline, semi-crystalline, amorphous, or a combination thereof.

[0060] According to one embodiment of this disclosure, the silicon-based active material comprises a carbon layer disposed on at least a portion of the porous carbon. For example, the carbon layer blocks the exposure of silicon to the outer surface of the porous carbon or reduces the reactivity of silicon, thereby preventing or suppressing the degradation of the lifetime characteristics of the silicon-carbon composite or gas generation due to contact with water during aqueous processes. Additionally, the carbon layer imparts conductivity to the silicon-based active material and can improve the initial efficiency, lifetime characteristics, and capacity characteristics of the secondary battery.

[0061] As a non-limiting example, the carbon layer may be formed before or after the formation of the coating comprising the metal oxide and the aqueous binder. Therefore, in the aforementioned core, the carbon layer may be disposed on a silicon-carbon composite core on which the coating is not disposed, or on at least a portion of the coating previously disposed on the silicon-carbon composite core. Furthermore, the carbon layer may completely surround the coating or may be formed only on a portion of the coating, thus both the coating and the carbon layer may be observed on the surface of the negative electrode active material.

[0062] According to one embodiment of this disclosure, the carbon layer can be formed prior to the formation of the coating comprising a metal oxide and a water-based binder. That is, the coating can be disposed on at least a portion of the carbon layer previously disposed on the silicon-carbon composite core. Furthermore, the coating can completely surround the carbon layer or can be formed only on a portion of the carbon layer, thus both the coating and the carbon layer can be observed on the surface of the negative electrode active material.

[0063] In one embodiment of this disclosure, the carbon layer may comprise at least one selected from amorphous carbon or crystalline carbon.

[0064] According to one embodiment, the carbon layer may be an amorphous carbon layer. The amorphous carbon maintains suitable strength of the carbon layer and inhibits the expansion of the silicon-carbon composite. Alternatively, the carbon layer may further comprise crystalline carbon, or it may not contain crystalline carbon.

[0065] The crystalline carbon can improve the conductivity of the negative electrode active material. The crystalline carbon may contain at least one selected from fullerenes, carbon nanotubes, and graphene.

[0066] The amorphous carbon maintains suitable strength of the carbon layer and inhibits the expansion of the silicon-carbon composite. The amorphous carbon can be a carbonaceous material formed by carbonization of at least one of tar, pitch, and other organic substances, or by using hydrocarbons as a source in chemical vapor deposition.

[0067] Carbonized organic matter may include carbonized sucrose, glucose, galactose, fructose, lactose, mannose, ribose, aldose, or hexylose or combinations thereof.

[0068] The hydrocarbon may be a substituted or unsubstituted aliphatic or alicyclic hydrocarbon, or a substituted or unsubstituted aromatic hydrocarbon. The substituted or unsubstituted aliphatic or alicyclic hydrocarbon may be methane, ethane, ethylene, acetylene, propane, butane, butene, pentane, isobutane, or hexane. The substituted or unsubstituted aromatic hydrocarbon may be benzene, toluene, xylene, styrene, ethylbenzene, diphenylmethane, naphthalene, phenol, cresol, nitrobenzene, chlorobenzene, indene, coumarone, pyridine, anthracene, or phenanthrene.

[0069] In one embodiment of this disclosure, based on 100 parts by weight of the silicon-based active material, the carbon layer content can be from about 0.1 parts by weight to 50 parts by weight, from about 0.1 parts by weight to 30 parts by weight, or from about 0.1 parts by weight to 20 parts by weight. For example, the carbon layer content can be from about 0.5 parts by weight to 15 parts by weight or from about 1 part by weight to 10 parts by weight. When the above ranges are met, conductivity is improved, and the capacity and efficiency of the silicon-based active material are also improved.

[0070] In one embodiment of this disclosure, the carbon layer has a thickness of about 1 nm to 500 nm, for example, 5 nm to 300 nm or 5 nm to 100 nm. When the above range is met, the conductivity of the silicon-based active material is improved, the volume change of the silicon-based active material is effectively suppressed, and the side reactions between the electrolyte and the silicon-based active material are suppressed, thereby improving the initial efficiency and / or lifespan of the battery.

[0071] According to one embodiment, the carbon layer can be formed by a chemical vapor deposition (CVD) method using at least one hydrocarbon gas selected from methane, ethane, and acetylene.

[0072] According to another embodiment of this disclosure, the Si / C (silicon-carbon composite) can be configured such that carbon is coated on the surface of the silicon or silicon oxide particles by calcination in a state where the carbon is combined with silicon or silicon oxide particles, or that the carbon is dispersed in the silicon particles in an atomic state, or that the core obtained by silicon and carbon composite is surrounded by graphite, graphene or amorphous carbon.

[0073] According to one embodiment of this disclosure, when the silicon-based active material comprises Si / C, the Si:C atomic ratio on the surface of the silicon-based active material is about 1:1 to 1:4, for example, about 1:2 to 1:4 or 1:3 to 1:4. Since the silicon-based active material has a carbon layer on its surface, the carbon ratio at the surface is higher. This atomic ratio indicates that the carbon coating on the surface of the silicon-based active material is sufficient, and the ratio can be measured by XPS. The atomic ratio can be adjusted by controlling the amount of carbide material during the introduction of the carbon layer or by changing the calcination time.

[0074] According to one embodiment of this disclosure, when the silicon-based active material comprises Si / C, the Si:C atomic ratio in the silicon-based active material can be from about 0.9:1.1 to 1.1:0.9, for example, from about 1:0.95 to 1:1.1. This range of Si:C atomic ratios is advantageous for meeting requirements for capacity, lifetime, and processability. The Si / C is primarily composed of two elements (Si and C). Therefore, while excluding the influence of other elements, the C content can be measured using a CS analyzer, and the Si content can then be calculated by subtracting the C content from the total amount.

[0075] The Si / C can be manufactured by a method including the following steps: forming a core comprising the silicon-carbon composite and forming a carbon layer on at least a portion of the core.

[0076] According to one embodiment, the step of forming a core comprising the silicon-carbon composite can be performed by etching carbon particles (e.g., porous carbon) containing internal pores to enlarge the internal pores of the carbon particles, and forming silicon particles on the surface of the carbon particles and in the enlarged internal pores.

[0077] The step of enlarging the internal pores of the carbon particles can be carried out in a nitrogen (N2) atmosphere, an oxygen (O2) atmosphere, or an air atmosphere. For example, the flow rate of oxygen (O2) or oxygen-containing air can be controlled to be from about 0.1 L / min to 10 L / min.

[0078] The step of enlarging the internal pores of the carbon particles can be carried out at a temperature of about 400°C to 1,200°C for 30 minutes to 4 hours.

[0079] The pore properties of the obtained porous carbon particles can vary depending on the conditions that enlarge the internal pores of the carbon particles.

[0080] To enlarge the internal pores of the carbon particles, an etchant, such as an alkaline material like KOH, can be used. For example, the carbon particles and KOH can be mixed in a weight ratio of about 1:1 to 1:5 to enlarge the internal pores of the carbon particles.

[0081] The formation of the silicon particles can be performed using a chemical vapor deposition (CVD) method. In this case, silicon nanoparticles are deposited on the surface and / or within the internal pores of carbon particles in which the internal pores are enlarged, thereby forming a silicon coating in the form of a film, an island, or a combination thereof.

[0082] The silicon particles can be formed by introducing SiH4 / H2 gas into a CVD apparatus at a temperature of about 500°C to 900°C for deposition on the carbon particles, thereby forming the silicon-carbon composite.

[0083] The step of forming the carbon layer can be performed by chemical vapor deposition (CVD) using carbonaceous materials (e.g., hydrocarbon gases) or by carbonizing the material used as the carbon source.

[0084] For example, after introducing the core containing the silicon-carbon composite into the reactor, a hydrocarbon gas can be subjected to chemical vapor deposition (CVD) at about 600°C to 700°C to form the carbon layer. The hydrocarbon gas may be at least one hydrocarbon gas selected from methane, ethane, propane, and acetylene.

[0085] In one embodiment of this disclosure, the coating contained in the negative electrode active material together with the silicon-based active material comprises a metal oxide and a water-based binder.

[0086] Because the metal oxide is characterized by high hardness, the coating containing the metal oxide improves the durability of the silicon-based active material and suppresses the rapid volume expansion of the silicon-based active material during operation.

[0087] According to one embodiment of this disclosure, the metal oxide can be represented by Formula 1: [Formula 1] M a O b (1≤a≤2,1≤b≤5) In Formula 1, M is any one of Al, Ti, and Mg. When M in Formula 1 is any one of Al, Ti, and Mg, a coating can be formed on the silicon-based active material to reduce volume expansion without degrading the performance of the secondary battery. For example, when the metal oxide in Formula 1 contains Zn, Fe, Cu, Ni, Sn, Sb, Cr, Zr, or V, depending on the metal's operating voltage range, a short circuit may occur due to metal dissolution, leading to a decrease in the battery's operating voltage. Therefore, M can be any one selected from Al, Ti, and Mg.

[0088] In one embodiment of this disclosure, the metal oxide may contain at least one selected from Al2O3, TiO2, and MgO. When the metal oxide contains such components, a coating can be formed on the silicon-based active material to reduce volume expansion without degrading the performance of the secondary battery.

[0089] In one embodiment of this disclosure, the metal oxide may contain at least one selected from Al2O3, TiO2 and MgO, for example, the metal oxide may be Al2O3.

[0090] According to one embodiment of this disclosure, the metal oxide may have an average particle size (D50) of about 1 nm to 100 nm. For example, the average particle size (D50) of the metal oxide may be 1 nm or more, 2 nm or more, 100 nm or less, 80 nm or less, 50 nm or less, 30 nm or less, or 20 nm or less. When the average particle size (D50) of the metal oxide falls within the above range and the metal oxide is in the form of nanoparticles, a uniform coating can be formed on the surface of the active material without hindering the migration of lithium ions in a single-cell operating environment.

[0091] The average particle size of the metal oxide is the volume average of the diameters (equivalent spherical diameters) obtained by converting each metal oxide particle into a sphere of the same volume, and this value can be determined by observation with an electron microscope. For example, when observing the metal oxide with an electron microscope, the value can be obtained by measuring the diameters of more than 200 metal oxide particles in a given field of view, calculating the equivalent spherical diameter of each particle, and averaging the calculated values.

[0092] The aqueous adhesive is flexible and, when included in the coating, reduces particle breakage even when the particle volume of the silicon-based active material expands. Furthermore, since the aqueous adhesive is mixed with the metal oxide within the coating, the adhesion between the silicon-based active material and the coating is improved.

[0093] Furthermore, during the aqueous process of preparing the negative electrode slurry, gases such as hydrogen may be generated in the case of the silicon-based active material, causing process problems. However, the negative electrode active material according to one embodiment of this disclosure includes the coating that blocks direct contact between the silicon-based active material core and the aqueous solvent (e.g., distilled water), thus reducing gas generation in the slurry during the aqueous process.

[0094] In this disclosure, the aqueous binder included in the coating differs from the negative electrode binder described later. According to one embodiment of this disclosure, the aqueous binder is contained within the coating disposed on the silicon-based active material particles. For example, the aqueous binder is located within the coating surrounding the silicon-based active material, while the negative electrode binder described later is uniformly dispersed in the negative electrode active material layer and observed between the negative electrode active material particles.

[0095] In one embodiment of this disclosure, the aqueous adhesive may comprise at least one of the following: polyacrylamide (PAM), polyacrylic acid (PAA), polyvinyl alcohol (PVA), polyethylene glycol (PEG), carboxymethyl cellulose (CMC), polyvinyl acetate (PVAc), polyvinylpyrrolidone (PVP), and substances thereof in which hydrogen is replaced by Li, Na, or Ca.

[0096] In one embodiment of this disclosure, the aqueous adhesive may comprise at least one selected from polyacrylamide (PAM), polyacrylic acid (PAA), and substances thereof in which hydrogen is replaced by Li, Na, or Ca.

[0097] For example, the aqueous adhesive may contain at least one selected from the following: polyacrylamide (PAM) and substances obtained by replacing hydrogen with Li, Na or Ca.

[0098] In one embodiment of this disclosure, the weight-average molecular weight (Mw) of the aqueous adhesive can be from about 1,000 g / mol to 1,000,000 g / mol. For example, the weight-average molecular weight (Mw) of the aqueous adhesive can be 1,000 g / mol or more, 10,000 g / mol or more, 50,000 g / mol or more, 100,000 g / mol or more, or 500,000 g / mol or more, and can be less than 1,000,000 g / mol, less than 800,000 g / mol, or less than 700,000 g / mol. When the weight-average molecular weight of the aqueous adhesive falls within the above range, the aqueous adhesive can be uniformly dispersed in the coating.

[0099] Figure 1 A negative electrode active material according to one embodiment of the present disclosure is shown. Reference Figure 1 A coating 2 is provided to surround at least a portion of the silicon-based active material 1, and the coating 2 contains a metal oxide 21 and an aqueous binder 22 mixed therein.

[0100] According to one embodiment of the present disclosure, the coating 2 is disposed on at least a portion of the silicon-based active material 1, for example, on at least a portion of the surface of the silicon-based active material.

[0101] The coating 2 may exist on the silicon-based active material 1 in the form of an island layer or a thin film layer, and is not limited to this, but may exist in various forms.

[0102] In one embodiment of this disclosure, since the coating 2 comprises both the aqueous binder 22 and the metal oxide 21, the adhesion between the silicon-based active material 1 and the coating 2 is excellent compared to forming a coating using only the metal oxide or only the aqueous binder, and a thin and uniform coating can be formed. When the coating 2 comprises only the metal oxide 21, the metal oxide may not be uniformly dispersed, resulting in uneven formation. When the coating 2 comprises only the aqueous binder 22, the coating may not be formed on the silicon-based active material 1.

[0103] According to one embodiment of this disclosure, the coating 2 may comprise the metal oxide 21 and the aqueous binder 22 in a weight ratio of about 50:50 to 95:5, for example, a weight ratio of about 70:30 to 90:10. For example, the coating 2 may comprise the metal oxide 21 and the aqueous binder 22 in a weight ratio of more than about 70:30 and less than about 90:10, or less than 85:15.

[0104] When the contents of the metal oxide 21 and the aqueous binder 22 are within the above range, the coating 2 can fully act as a resist on the surface of the silicon-based active material 1, can form the coating uniformly, and can improve battery performance.

[0105] Another feature of this disclosure is that by optimizing the weight ratio of the metal oxide 21 to the aqueous binder 22 in the coating 2 as described above, performance degradation due to particle expansion of the silicon-based active material 1 can be prevented or suppressed without affecting the migration or behavior of lithium ions.

[0106] According to one embodiment of this disclosure, the coating 2 may have an average thickness of about 100 nm to 1 μm. For example, the average thickness of the coating 2 may be 200 nm or more, 230 nm or more, 250 nm or more, or 280 nm or more, and may be less than 1 μm, less than 500 nm, or less than 400 nm. The fact that the average thickness of the coating 2 falls within the above-mentioned range means that the coating 2 is disposed on at least a portion of the silicon-based active material 1, and that more than 50% of the coating 2 has a thickness within the range.

[0107] When the average thickness of the coating 2 falls within the aforementioned range, it can prevent the silicon-based active material 1 from being exposed to the outside, or it can increase the physical resistance of the silicon-based active material itself, thereby preventing or suppressing deterioration caused by the volume expansion and particle breakage of the silicon-based active material. Additionally, when the thickness of the coating 2 falls within the aforementioned range, it can prevent direct contact between the core of the silicon-based active material 1 and the aqueous solvent, thereby reducing the generation of undesirable gases (e.g., hydrogen (H2)) in the slurry during aqueous processes and improving processability.

[0108] The thickness of the coating 2 can be measured by cross-sectional analysis of the negative electrode containing the negative electrode active material 1, and the cross-sectional analysis of the negative electrode can be performed using an ion milling apparatus. For example, a Hitachi IM4000 apparatus can be used to mill the electrode sample. After irradiating each sample with an ion beam at 1.5 kV for approximately 3 to 4 hours, cross-sectional images can be measured using a Hitachi S-4800 SEM. Individual particles observed in each SEM image obtained from the cross-section can be measured, and the average thickness of the coating 2 measured from each cross-sectional image, obtained by randomly selecting five regions of the cross-section and capturing images at 10K magnification, can be used.

[0109] In one embodiment of this disclosure, the negative electrode active material 1 may have an average particle size (D50) of about 1 μm to 20 μm. When the average particle size falls within this range, the specific surface area of ​​the particles does not increase excessively, and the viscosity of the negative electrode slurry does not increase excessively. Therefore, it can help disperse the particles constituting the negative electrode slurry. In addition, when the average particle size falls within the above range, the contact area between the silicon particles and the conductive material is appropriately maintained by the composite of the conductive material and the binder in the negative electrode slurry, so that the conductive network does not break and the capacity retention is improved. Furthermore, when the average particle size falls within the above range, there are no excessively large silicon particles, thereby making the surface of the negative electrode smooth and preventing non-uniformity of current density during charging and discharging. In addition, the phase stability of the negative electrode slurry can be improved, and the processability can be improved. As a result, the capacity retention of the battery can be improved.

[0110] The “average particle size (D50) of the negative electrode active material” is different from the “average particle size (D50) of the silicon-based active material”. It refers to the average particle size (D50) of the final negative electrode active material on which a coating is provided.

[0111] negative electrode composition

[0112] One embodiment of this disclosure provides a negative electrode composition comprising a negative electrode active material according to one embodiment of this disclosure.

[0113] The negative electrode composition may further comprise additional negative electrode active material. As said additional negative electrode active material, compounds capable of reversibly inserting and de-intercalating lithium can be used. Examples include carbon-based materials such as artificial graphite, natural graphite, graphitized carbon fibers, and amorphous carbon; metal compounds capable of forming alloys with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; and metal oxides capable of doping and de-doping lithium, such as SiO₂. β (0<β<2), SnO2, vanadium oxide, lithium titanium oxide, lithium vanadium oxide; or composites containing the above metal compounds and carbon-based materials, such as Si-C composites or Sn-C composites, and these can be used alone or in mixtures of two or more thereof. Furthermore, lithium metal films can also be used as the negative electrode active material. Additionally, both low-crystallinity carbon and high-crystallinity carbon can be used as carbon materials. Representative examples of low-crystallinity carbon include soft carbon and hard carbon, and representative examples of high-crystallinity carbon include amorphous, plate-like, flake-like, spherical, or fibrous natural or artificial graphite, floating graphite, pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microspheres, mesophase pitch, and high-temperature calcined carbon such as coke derived from petroleum or coal tar pitch.

[0114] One embodiment of this disclosure provides a negative electrode composition, the negative electrode composition further comprising a carbon-based active material as the negative electrode active material. The carbon-based active material comprises at least one selected from natural graphite and artificial graphite.

[0115] According to one embodiment of this disclosure, the additional negative electrode active material may be a carbon-based active material. The carbon-based active material may be graphite, and the graphite may comprise at least one selected from natural graphite and synthetic graphite.

[0116] The carbon-based active material can be natural graphite, artificial graphite, or a mixture of natural and artificial graphite.

[0117] The artificial graphite is typically prepared by carbonizing raw materials such as coal tar, coal tar pitch, or heavy petroleum oil at temperatures above 2,500°C. After graphitization, the particle size is adjusted through processes such as crushing and secondary particle formation to suit its use as a negative electrode active material. In the case of artificial graphite, crystals are randomly distributed within the particles, exhibiting lower sphericity compared to natural graphite, and the particles have a slightly pointed shape.

[0118] Additionally, the artificial graphite may have an average particle size (D) of about 5 μm to 30 μm, for example, about 10 μm to 25 μm. 50 ).

[0119] The natural graphite is typically in the form of plate-like aggregates before processing, and the plate-like particles are processed by post-processing such as crushing and reassembly to obtain spherical particles with smooth surfaces for use as active materials in electrode manufacturing.

[0120] In addition, the natural graphite may have a particle size of about 5 μm to 30 μm or about 10 μm to 25 μm.

[0121] When the carbon-based active material is a mixture of artificial graphite and natural graphite, the weight ratio of the artificial graphite to the natural graphite can be from about 9.99:0.01 to 0.01:9.99 or from about 9.7:0.3 to 7:3. When the weight ratio falls within the above range, excellent output can be exhibited.

[0122] When the silicon-based anode active material according to one embodiment of this disclosure is referred to as the first anode active material and the additional carbon-based anode active material is referred to as the second anode active material, the content of the first anode active material may be from about 1 part by weight to 30 parts by weight, based on a total of 100 parts by weight of the first anode active material and the second anode active material. For example, based on a total of 100 parts by weight of the first anode active material and the second anode active material, the content of the first anode active material may be more than 1 part by weight or more than 2 parts by weight, and may be less than 30 parts by weight, less than 25 parts by weight, less than 20 parts by weight, or less than 15 parts by weight.

[0123] In one embodiment of this disclosure, based on a total of 100 parts by weight of the first negative electrode active material and the second negative electrode active material, the content of the second negative electrode active material may be about 70 parts by weight or more. For example, based on a total of 100 parts by weight of the first negative electrode active material and the second negative electrode active material, the content of the second negative electrode active material may be 70 parts by weight or more, 75 parts by weight or more, 80 parts by weight or more, 90 parts by weight or more, 98 parts by weight or more, or 99 parts by weight or more, and may be less than 100 parts by weight, less than 100 parts by weight, less than 99 parts by weight, less than 97 parts by weight, or less than 95 parts by weight.

[0124] Since the first negative electrode active material, namely the silicon-based negative electrode active material 1 according to one embodiment of the present disclosure, includes the coating 2 which can prevent or suppress volume expansion and particle breakage during charge and discharge, the content of the first negative electrode active material including the silicon-based negative electrode active material 1 with significantly high capacity can be within the above-mentioned range. Therefore, excellent output characteristics and capacity during charge and discharge can be achieved without reducing the negative electrode performance.

[0125] In one embodiment of this disclosure, the negative electrode composition further comprises a negative electrode binder.

[0126] In one embodiment of this disclosure, the negative electrode adhesive comprises an aqueous adhesive.

[0127] In one embodiment of this disclosure, the negative electrode adhesive may comprise at least one selected from the following: polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, polyacrylamide (PAM), and materials thereof with hydrogen substituted by Li, Na, or Ca, and may also comprise various copolymers thereof.

[0128] According to one embodiment of this disclosure, the negative electrode adhesive is used to retain the active and conductive materials to prevent or suppress distortion or structural deformation of the negative electrode structure. Any general-purpose adhesive can be applied as long as these functions are satisfied, and in one embodiment, a water-based adhesive may be used.

[0129] In one embodiment of this disclosure, the negative electrode adhesive comprises an aqueous adhesive, and the content of the negative electrode adhesive may be from about 1 part by weight to 10 parts by weight based on 100 parts by weight of the negative electrode composition.

[0130] In another embodiment of this disclosure, based on 100 parts by weight of the negative electrode composition, the content of the negative electrode adhesive may be more than 1 part by weight, more than 2 parts by weight, or more than 2.5 parts by weight, and may be less than 3 parts by weight, less than 10 parts by weight, less than 7 parts by weight, less than 5 parts by weight, or less than 3 parts by weight.

[0131] In the negative electrode according to this disclosure, in order to maximize capacity characteristics, the silicon-based negative electrode active material 1 or its modified form is used in the above-mentioned parts by weight, which results in greater volume expansion during charge and discharge compared to a secondary battery that uses only carbon-based active materials. Therefore, by including the negative electrode binder in the above-mentioned content range, the negative electrode binder can effectively limit the volume expansion of the rigid silicon-based active material 1 during charge and discharge.

[0132] In one embodiment of this disclosure, the negative electrode composition further comprises a negative electrode binder and a negative electrode conductive material.

[0133] In one embodiment of this disclosure, the conductive material may include at least one selected from point-like conductive materials, planar conductive materials, and linear conductive materials.

[0134] In one embodiment of this disclosure, the dot-shaped conductive material can be used to improve the conductivity of the negative electrode, and refers to a spherical or dot-shaped conductive material that is conductive without causing chemical changes. For example, the dot-shaped conductive material may comprise at least one selected from the following: natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking black, conductive fibers, fluorocarbons, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, or may comprise carbon black for the purpose of achieving high conductivity and excellent dispersibility.

[0135] In one embodiment of this disclosure, the dot-shaped conductive material may have a diameter of approximately 40 μm. 2 / g to 70m 2 / g, for example, about 45m 2 / g to 65m 2 / g or approximately 50m 2 / g to 60m 2 / g BET specific surface area.

[0136] In one embodiment of this disclosure, the conductive material may comprise a planar conductive material.

[0137] The planar conductive material can be used to increase the surface contact between silicon particles in the negative electrode to improve conductivity, while suppressing the disconnection of the conductive path caused by volume expansion, and can be described as a plate-shaped conductive material or a bulk-shaped conductive material.

[0138] In one embodiment of this disclosure, the planar conductive material may comprise at least one selected from plate graphite, graphene, graphene oxide, and graphite flakes, or may be plate graphite.

[0139] In one embodiment of this disclosure, the average particle size (D50) of the planar conductive material can be from about 2 μm to 7 μm, for example, from about 3 μm to 6 μm or from about 4 μm to 5 μm. When the above range is met, the particle size is sufficient to promote dispersion without causing an excessive increase in the viscosity of the negative electrode slurry. Therefore, when dispersion is performed using the same equipment and time, the dispersion effect is excellent.

[0140] In one embodiment of this disclosure, the planar conductive material may be a high specific surface area planar conductive material with a high BET specific surface area; or a low specific surface area planar conductive material.

[0141] In one embodiment of this disclosure, either a high specific surface area planar conductive material or a low specific surface area planar conductive material can be used as the planar conductive material, without any limitation. However, since the planar conductive material according to this disclosure may be affected to some extent by dispersion on electrode performance, a low specific surface area planar conductive material that does not cause dispersion problems can be used.

[0142] In one embodiment of this disclosure, the planar conductive material may have a surface area of ​​approximately 5 μm. 2 BET specific surface area above / g.

[0143] In another embodiment, the planar conductive material may have a surface area of ​​approximately 5 μm. 2 / g or more and 500m 2 / g or less, for example, about 5m 2 / g or more and 300m 2 / g or about 5m 2 / g or more and 250m 2 BET specific surface area below / g.

[0144] In another embodiment, the planar conductive material is a high specific surface area planar conductive material, and may have a surface area of ​​approximately 50 μm. 2 / g to 500m 2 / g, or approximately 80m 2 / g to 300m 2 / g, or approximately 100mg 2 / g to 300m 2 BET specific surface area within the range of / g.

[0145] In yet another embodiment, the planar conductive material is a low specific surface area planar conductive material, and can have a surface area of ​​approximately 5m². 2 / g to 40m 2 / g, for example, about 5m 2 / g to 30m 2 / g, or approximately 5m 2 / g to 25m 2 BET specific surface area within the range of / g.

[0146] Other conductive materials may include linear conductive materials, such as carbon nanotubes. The carbon nanotubes may be bundled carbon nanotubes. A bundled carbon nanotube may comprise multiple carbon nanotube units. Here, unless otherwise stated, the term "bundled" refers to a secondary shape in the form of a bundle or rope, wherein multiple carbon nanotube units are arranged parallel to or entangled in an orientation substantially the same as the longitudinal axis of the carbon nanotube units. The carbon nanotube units have cylindrical graphite sheets and sp... 2Bonded structure. At this point, depending on the angle and structure of the graphite sheet winding, it can exhibit conductor or semiconductor properties. Compared to entangled carbon nanotubes, the bundled carbon nanotubes can be uniformly dispersed during anode fabrication and can smoothly form a conductive network within the anode, thereby improving the conductivity of the anode.

[0147] In one embodiment of this disclosure, the linear conductive material may comprise SWCNT or MWCNT.

[0148] In one embodiment of this disclosure, a negative electrode composition is provided, wherein, based on 100 parts by weight of the negative electrode slurry, the amount of the negative electrode conductive material present is more than about 0.01 parts by weight and less than 10 parts by weight.

[0149] In another embodiment, based on 100 parts by weight of the negative electrode composition, the content of the negative electrode conductive material may be more than about 0.01 parts by weight or more than 0.05 parts by weight, and may be less than about 10 parts by weight, less than 5 parts by weight, or less than 3 parts by weight.

[0150] The negative electrode conductive material according to this disclosure has a completely different structure from the positive electrode conductive material used in the positive electrode. For example, the negative electrode conductive material according to this disclosure serves to maintain the contact points between silicon-based active materials that expand greatly in electrode volume due to charging and discharging, while the positive electrode conductive material serves to act as a buffer during rolling and provide a certain degree of conductivity. Therefore, their structures and functions are completely different from those of the negative electrode conductive material in this disclosure.

[0151] Furthermore, the negative electrode conductive material according to this disclosure is applied to silicon-based active materials, and therefore has a completely different composition from the conductive material applied to a negative electrode composition containing only graphite-based active materials. For example, the conductive material used in an electrode containing graphite-based active materials simply has smaller particles compared to the active materials, and therefore has the properties of improving output characteristics and imparting a certain conductivity, and is completely different in structure and function from the negative electrode conductive material used in conjunction with silicon-based active materials as described in this disclosure.

[0152] negative electrode

[0153] Figure 2 A stacked structure of the negative electrode according to one embodiment of the present disclosure is shown.

[0154] refer to Figure 2 According to one embodiment of the present disclosure, the negative electrode 100 includes a negative electrode current collector layer 10 and a negative electrode active material layer 20 disposed on one or two surfaces of the negative electrode current collector layer 10, wherein the negative electrode active material layer 20 includes a negative electrode composition according to one embodiment of the present disclosure.

[0155] Figure 2 The diagram shows the negative electrode active material layer 20 formed on one surface of the negative electrode current collector layer 10. However, this disclosure is not limited thereto; for example, the negative electrode active material layer 20 may be formed on both surfaces of the negative electrode current collector layer 10.

[0156] In one embodiment of this disclosure, the negative electrode 100 can be formed by coating a negative electrode slurry containing the negative electrode composition onto one or both sides of the negative electrode current collector layer 10 and drying it.

[0157] At this time, the negative electrode slurry may contain the negative electrode composition and the slurry solvent.

[0158] In one embodiment of this disclosure, the solids content of the negative electrode slurry can be in the range of about 5% to 60%. In another embodiment, the solids content of the negative electrode slurry can be in the range of about 5% to 60%, for example about 7% to 50%, or about 10% to 50%.

[0159] The solid content of the negative electrode slurry can refer to the content of the negative electrode composition contained in the negative electrode slurry, and can be expressed as the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.

[0160] When the solid content of the negative electrode slurry is within the above range, the viscosity during the formation of the negative electrode active material layer is suitable, minimizing particle aggregation of the negative electrode composition and enabling the effective formation of the negative electrode active material layer.

[0161] In one embodiment of this disclosure, a slurry solvent may be used without limitation, as long as the slurry solvent is capable of dissolving the negative electrode composition, and examples may include water or NMP (N-methyl-2-pyrrolidone).

[0162] In one embodiment of this disclosure, the negative electrode current collector layer 10 has a thickness of about 1 μm to 100 μm. There are no particular limitations on the negative electrode current collector layer 10, as long as it has high conductivity without causing chemical changes in the battery, and examples include copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel with a surface treated with carbon, nickel, titanium, or silver, and aluminum-cadmium alloys. Furthermore, the negative electrode current collector layer may have fine irregularities formed on its surface to enhance the bonding strength of the negative electrode active material, and can be used in various forms such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.

[0163] In one embodiment of this disclosure, the negative electrode 100 is provided such that the negative electrode current collector layer 10 has a thickness of about 1 μm to 100 μm, and the negative electrode active material layer 20 has a thickness of about 5 μm to 500 μm.

[0164] However, the thicknesses of the negative electrode current collector layer 10 and the negative electrode active material layer 20 can be varied according to the type and application of the negative electrode 100, and are not limited thereto.

[0165] In one embodiment of this disclosure, there is no particular limitation on the porosity of the negative electrode active material layer 20, but it can be in the range of about 10% to 60%.

[0166] In another embodiment, the porosity of the negative electrode active material layer 20 may be more than about 10% and less than 60%, for example, more than about 20% and less than 50%, or more than about 30% and less than 45%.

[0167] The porosity can vary depending on the composition and content of the negative electrode active material, conductive material, and binder contained in the negative electrode active material layer 20. For example, by including negative electrode active material and conductive material according to this disclosure with specific compositions and contents, the porosity can meet the above-mentioned range, thereby providing the electrode with a suitable range of conductivity and resistance.

[0168] Secondary batteries

[0169] Figure 3 A stacked structure of a secondary battery according to one embodiment of the present disclosure is shown.

[0170] refer to Figure 3 A secondary battery 300 according to one embodiment of the present disclosure includes a positive electrode 200, a negative electrode 100 according to one embodiment of the present disclosure, a separator 30 disposed between the positive electrode 200 and the negative electrode 100, and an electrolyte (not shown).

[0171] A secondary battery 300 according to one embodiment of the present disclosure includes a negative electrode 100 having a negative electrode active material layer 20 on one surface of a negative electrode current collector layer 10; and a positive electrode 200 having a positive electrode active material layer 40 on one surface of a positive electrode current collector layer 50. The positive electrode 200 and the negative electrode 100 are stacked together with a separator 30 inserted therebetween.

[0172] The positive electrode 200 may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, the positive electrode active material layer containing a positive electrode active material.

[0173] In the positive electrode 200, there are no particular limitations on the positive electrode current collector, as long as it is conductive and will not cause chemical changes in the battery. Examples of such materials include stainless steel, aluminum, nickel, titanium, calcined carbon, and aluminum or stainless steel with a surface treated with carbon, nickel, titanium, or silver. The positive electrode current collector can typically have a thickness of about 3 μm to 500 μm, and fine irregularities can be formed on the surface of the positive electrode current collector to enhance the adhesion strength of the positive electrode active material. For example, the positive electrode current collector can be used in various forms such as films, sheets, foils, meshes, porous bodies, foams, nonwoven fabrics, etc.

[0174] The positive electrode active material can be a commonly used positive electrode active material. For example, the positive electrode active material can be a layered compound, such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound replaced by one or more transition metals; lithium iron oxide, such as LiFe3O4; lithium manganese oxide, such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides, such as LiV3O8, V2O5 and Cu2V2O7; Ni-site type lithium nickel oxides, consisting of the chemical formula LiNi 1-c2 M c2 O2 (where M is at least one selected from Co, Mn, Al, Cu, Fe, Mg, B, and Ga, and satisfies 0.01 ≤ c2 ≤ 0.3) represents the lithium manganese composite oxide, represented by the chemical formula LiMn 2-c3 M c3 O2 (wherein M is at least one selected from Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01 ≤ c3 ≤ 0.1) or Li2Mn3MO8 (wherein M is at least one selected from Fe, Co, Ni, Cu, and Zn); LiMn2O4, wherein a portion of the Li in the chemical formula is replaced by an alkaline earth metal ion; however, this disclosure is not limited thereto. According to one embodiment, the positive electrode may be Li metal.

[0175] Based on the above-mentioned positive electrode active material, the positive electrode active material layer may also include a positive electrode conductive material and a positive electrode binder.

[0176] The positive electrode conductive material used to impart conductivity to the electrode can be any material that is conductive without causing a chemical change in the battery to be constructed, without any particular limitation. Examples include graphite, such as natural or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking black, and carbon fibers; metal powders or fibers such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide or potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, which can be used alone or in mixtures of two or more thereof.

[0177] In addition, the positive electrode adhesive is used to improve the adhesion between the positive electrode active material particles and the adhesion strength between the positive electrode active material and the positive electrode current collector. Examples include polyvinylidene fluoride (PVDF), PVDF-co-HFP copolymer, polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, which may be used alone or in mixtures of two or more thereof.

[0178] The separator 30 separates the negative electrode 100 from the positive electrode 200 and provides a migration channel for lithium ions. Any separator commonly used in secondary batteries can be used; there are no particular limitations. Any material with low resistance to ion migration in the electrolyte and excellent electrolyte retention can be used. For example, the separator can be a porous polymer membrane, such as a porous polymer membrane made of polyolefin polymers like ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer, or a laminated structure of two or more layers thereof. Alternatively, conventional porous nonwoven fabrics can be used, such as nonwoven fabrics made of high-melting-point glass fibers, polyethylene terephthalate fibers, etc. Furthermore, coated separators containing ceramic components or polymer materials can be used to ensure heat resistance or mechanical strength, and can be selectively used in single-layer or multi-layer structures.

[0179] The electrolytes used in this disclosure may include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc., which can be used to manufacture lithium secondary batteries 300.

[0180] The electrolyte may contain non-aqueous organic solvents and metal salts.

[0181] Examples of the non-aqueous organic solvents include aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butyl carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triphosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0182] Among carbonate-based organic solvents, cyclic carbonates such as ethylene carbonate and propylene carbonate are high-viscosity organic solvents with high dielectric constants, and are therefore preferred due to their efficient dissociation of lithium salts. When such cyclic carbonates are mixed with linear carbonates such as dimethyl carbonate and diethyl carbonate, which have low viscosity and low dielectric constants, electrolytes with high conductivity can be obtained.

[0183] The metal salt may be a lithium salt, and the lithium salt is a substance readily soluble in non-aqueous electrolytes. For example, the anion of the lithium salt may be at least one selected from the following: F - Cl - I - NO3 - N(CN)2 - BF4 - ClO4 - PF6 - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 - (CF3)5PF - (CF3)6P - CF3SO3 - CF3CF2SO3 - (CF3SO2)2N - (FSO2)2N - CF3CF2(CF3)2CO - (CF3SO2)2CH - (SF5)3C - (CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - CH3CO2 - SCN - and (CF3CF2SO2)2N - .

[0184] In addition to the electrolyte components, the electrolyte may further contain one or more additives for the purpose of improving battery life characteristics, suppressing battery capacity reduction, and improving battery discharge capacity, such as alkylene carbonate halide compounds like difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol dimethyl ether, hexamethylphosphoryltriamine, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolides, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride.

[0185] Battery modules and battery packs

[0186] One embodiment of this disclosure provides a battery module that includes a secondary battery 300 according to one embodiment of this disclosure.

[0187] One embodiment of this disclosure provides a battery pack including a secondary battery 300 according to one embodiment of this disclosure.

[0188] One embodiment of this disclosure provides a battery pack that includes a battery module according to one embodiment of this disclosure.

[0189] One embodiment of this disclosure provides a battery module comprising the secondary battery 300 as a unit cell, and a battery pack comprising the secondary battery 300 or the battery module. Because the battery module and the battery pack comprise the secondary battery 300, which has high capacity, high rate capability, and high cycle performance, they can be used as a power source for medium to large-sized devices selected from electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems.

[0190] The following embodiments are provided to aid in understanding this disclosure; however, these embodiments are merely examples of this disclosure, and those skilled in the art will understand that various modifications and variations can be made within the spirit and scope of this disclosure. It should be understood that such modifications and variations fall within the scope of the appended claims.

[0191] Methods of implementing the invention

[0192] <Preparation Example>

[0193] <Example 1>

[0194] 1) Preparation of negative electrode active materials

[0195] Alumina (Al₂O₃, average particle size (D50) = 11 nm) was prepared as the metal oxide, and polyacrylamide (PAM, weight average molecular weight (Mw) = 650,000 g / mol) was prepared as the aqueous binder, with a metal oxide to aqueous binder ratio of 80:20 parts by weight. The metal oxide, the aqueous binder, and silicon-based active material (pure Si powder, average particle size (D50) = 2.95 μm) were prepared in a weight ratio of 95:4:1 and introduced into distilled water as a solvent to form a coating composition. The coating composition was loaded into a ball mill (planetary ball mill, Pulverisette 5, manufactured by Laval Labs) and wet-milled at 1,000 rpm for 6 hours. After wet milling, the coating composition was filtered, and the obtained solid was vacuum-dried at 120°C for 24 hours to remove residual solvent from the surface, thereby producing a powdered negative electrode active material in which a coating is formed on the surface of the silicon-based active material.

[0196] The manufactured negative electrode active material has an average particle size (D50) of 3.7 μm and the coating has an average thickness of 350 nm.

[0197] 2) Preparation of negative electrode slurry

[0198] The negative electrode active material obtained in Preparation 1) of Example 1 was used as the first negative electrode active material, while natural graphite (average particle size (D50) = 17 μm) was used as the second negative electrode active material. The two were mixed in a 5:95 ratio to prepare a negative electrode active material mixture. Based on 100 parts by weight of the negative electrode composition, 96 parts by weight of the negative electrode active material mixture, 0.85 parts by weight of SWCNT (single-walled carbon nanotubes) as a conductive material, and 1.7 parts by weight of polyacrylamide (PAM), 1.4 parts by weight of SBR, and 0.05 parts by weight of CMC (total 3.15 parts by weight of binder) as a binder were prepared, and these components were added to distilled water as a solvent to prepare a negative electrode slurry with a solids content of 46% by weight.

[0199] For example, SWCNT, PAM, SBR, and CMC were dispersed in distilled water using a homogenizer (2,500 rpm, 30 minutes). The negative electrode active material mixture was then added and dispersed at 2,500 rpm for 30 minutes to prepare the negative electrode slurry.

[0200] The SWCNTs used have a range of 1,000 to 1,500 m 2 It has a BET specific surface area of ​​ / g and an aspect ratio of over 10,000, and is used in the form of a solution dispersed in carboxymethyl cellulose (CMC).

[0201] The PAM is in aqueous form, with a weight-average molecular weight (Mw) of 500,000 g / mol to 800,000 g / mol, a number-average molecular weight (Mn) of 100,000 to 400,000, and a PDI value of 10 to 30. The weight-average molecular weight and number-average molecular weight of the aqueous adhesive are measured using aqueous gel permeation chromatography (GPC).

[0202] 3) Preparation of the negative electrode

[0203] The negative electrode slurry was prepared at 189 mg / 25 cm⁻¹ 2 The loading amount is coated on both sides of a copper current collector (thickness: 15 μm) serving as the negative electrode current collector layer, rolled, and dried in a vacuum oven at 130 °C for 10 hours to form a negative electrode active material layer, thereby preparing the negative electrode (thickness: 65 μm).

[0204] 4) Preparation of secondary batteries

[0205] LiNi will be used as the positive electrode active material 0.6 Co 0.2 Mn 0.2 O2 (average particle size (D50): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent for forming the positive electrode slurry in a weight ratio of 97:1.5:1.5 to prepare a positive electrode slurry (solids concentration: 78 wt%).

[0206] The positive electrode slurry was prepared at 537 mg / 25 cm⁻¹ 2 The loading amount is coated on both sides of the aluminum current collector (thickness: 12μm) used as the positive electrode current collector, rolled (rolled), and dried in a vacuum oven at 130°C for 10 hours to form a positive electrode active material layer, thereby preparing the positive electrode (positive electrode thickness: 75μm).

[0207] A lithium secondary battery is prepared by inserting a polyethylene separator between the positive and negative electrodes and injecting an electrolyte.

[0208] The electrolyte is prepared by mixing fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) in a volume ratio of 10:90 to obtain an organic solvent, adding 3% by weight of vinylene carbonate (VC) based on the total weight of the electrolyte to the obtained organic solvent, and adding LiPF6 as a lithium salt at a concentration of 1M.

[0209] <Example 2>

[0210] Except for adjusting the mixing ratio of metal oxide to aqueous binder to 70:30 parts by weight in the preparation of the negative electrode active material in 1), the secondary battery was prepared in the same manner as in Example 1. The negative electrode active material prepared in the preparation of the negative electrode active material in 1) exhibited an average particle size (D50) of 3.7 μm and an average coating thickness of 350 nm.

[0211] <Example 3>

[0212] Except for adjusting the mixing ratio of metal oxide to aqueous binder to 90:10 parts by weight in the preparation of the negative electrode active material in 1), the secondary battery was prepared in the same manner as in Example 1. The negative electrode active material prepared in the preparation of the negative electrode active material in 1) exhibited an average particle size (D50) of 3.6 μm and an average coating thickness of 300 nm.

[0213] <Example 4>

[0214] Except for adjusting the mixing ratio of metal oxide to aqueous binder to 60:40 parts by weight in the preparation of the negative electrode active material in 1), the secondary battery was prepared in the same manner as in Example 1. The negative electrode active material prepared in the preparation of the negative electrode active material in 1) exhibited an average particle size (D50) of 3.7 μm and an average coating thickness of 350 nm.

[0215] <Example 5>

[0216] Except for adjusting the mixing ratio of metal oxide to aqueous binder to 95:5 parts by weight in the preparation of the negative electrode active material in 1), the secondary battery was prepared in the same manner as in Example 1. The negative electrode active material prepared in the preparation of the negative electrode active material in 1) exhibited an average particle size (D50) of 3.5 μm and an average coating thickness of 250 nm.

[0217] <Comparative Example 1>

[0218] Except for the use of silicon-based active material (pure Si powder, average particle size (D50) = 2.95 μm) as the negative electrode active material in 1), the secondary battery was prepared in the same manner as in Example 1. That is, Comparative Example 1 used uncoated silicon-based active material as the negative electrode active material.

[0219] <Comparative Example 2>

[0220] Alumina (Al₂O₃, average particle size (D50) = 11 nm) was prepared as the metal oxide. The metal oxide and silicon-based active material (pure Si powder, average particle size (D50) = 2.95 μm) were prepared in a weight ratio of 95:5 and introduced into distilled water as a solvent to form a coating composition. The coating composition was loaded into a ball mill (planetary ball mill, Pulverisette 5, manufactured by Laval Laboratories) and wet-milled at 1,000 rpm for 6 hours. After wet milling, the coating composition was filtered, and the obtained solids were vacuum-dried at 120 °C for 24 hours to remove residual solvent from the surface, thereby producing a powdered negative electrode active material in which a coating is formed on the surface of the silicon-based active material. The prepared negative electrode active material exhibited an average particle size (D50) of 3.1 μm and formed a coating with an average thickness of 50 nm non-uniformly.

[0221] Subsequently, a secondary battery was prepared in the same manner as in Example 1. That is, Comparative Example 2 used a negative electrode active material with a coating that does not contain an aqueous binder.

[0222] <Comparative Example 3>

[0223] Polyacrylamide (PAM, weight-average molecular weight (Mw) = 650,000 g / mol) was prepared as an aqueous binder. The aqueous binder and silicon-based active material (pure Si powder, average particle size (D50) = 2.95 μm) were prepared in a weight ratio of 95:5 and introduced into distilled water as a solvent to form a coating composition. The coating composition was loaded into a ball mill (planetary ball mill, Pulverisette 5, manufactured by Laval Laboratories) and wet-milled at 1,000 rpm for 6 hours. After wet milling, the coating composition was filtered, and the resulting solid was vacuum-dried at 120°C for 24 hours to remove residual solvent from the surface, thereby producing a powdered negative electrode active material in which a coating is formed on the surface of the silicon-based active material. The prepared negative electrode active material exhibited an average particle size (D50) of 3 μm, and the coating was almost invisible on the surface of the silicon-based active material, thus the coating thickness could not be measured.

[0224] Subsequently, a secondary battery was prepared in the same manner as in Example 1. That is, Comparative Example 3 used a negative electrode active material with a coating that does not contain metal oxides.

[0225] <Example 6>

[0226] A 0.5M sucrose aqueous solution was placed in an autoclave and reacted at 180°C for 24 hours to synthesize spherical particles. The resulting carbon particles were washed two to three times with ethanol and dried at 100°C for at least 12 hours. The dried carbon particles were then mixed with KOH at a weight ratio of 1:3 and heated at 800°C for 2 hours under a nitrogen atmosphere to expand the pores, thereby preparing porous carbon. The porous carbon was then washed with distilled water, dried at 100°C for at least 12 hours, and the resulting porous carbon with an oxide layer formed on it was placed in the hot zone of a CVD apparatus. A SiH4 / H2 = 5 / 95 gas was then flowed at 600°C at a flow rate of 50 ml / min for 2 hours to deposit silicon inside the porous carbon, thereby producing a Si / C (silicon-carbon composite). Subsequently, the Si / C composite was placed in the hot zone of the CVD equipment, and methane was introduced into the hot zone at 700°C for 1 hour using argon as a carrier gas to form a carbon layer on the surface, thereby preparing a silicon-based active material Si / C containing a surface carbon layer (average particle size (D50): 8.1 μm).

[0227] Subsequently, except that in the preparation of the negative electrode active material, the silicon-based active material (Si / C) prepared as described above was used instead of pure Si powder, the secondary battery was prepared in the same manner as in Example 1. The resulting negative electrode active material had an average particle size (D50) of 8.6 μm, and the average thickness of the coating was 270 nm.

[0228] <Example 7>

[0229] Except that the mixing ratio of metal oxide to aqueous binder was adjusted to 70:30 parts by weight in the preparation of the negative electrode active material in Example 6, the secondary battery was prepared in the same manner as in Example 6. The negative electrode active material prepared in the preparation of the negative electrode active material in Example 6 exhibited an average particle size (D50) of 8.7 μm and an average coating thickness of 300 nm.

[0230] <Example 8>

[0231] Except that the mixing ratio of metal oxide to aqueous binder was adjusted to 90:10 parts by weight in the preparation of the negative electrode active material in Example 6, the secondary battery was prepared in the same manner as in Example 6. The negative electrode active material prepared in the preparation of the negative electrode active material in Example 6 exhibited an average particle size (D50) of 8.7 μm and an average coating thickness of 280 nm.

[0232] <Example 9>

[0233] Except that the mixing ratio of metal oxide to aqueous binder was adjusted to 95:5 parts by weight in the preparation of the negative electrode active material in Example 6, the secondary battery was prepared in the same manner as in Example 6. The negative electrode active material prepared in the preparation of the negative electrode active material in Example 6 showed an average particle size (D50) of 8.6 μm and an average coating thickness of 230 nm.

[0234] <Comparative Example 4>

[0235] Except that in Example 6, 1) the negative electrode active material was prepared using a silicon-based active material (Si / C, average particle size (D50) = 8.1 μm) as the negative electrode active material, the secondary battery was prepared in the same manner as in Example 6. That is, Comparative Example 4 used an uncoated silicon-based active material as the negative electrode active material.

[0236] <Comparative Example 5>

[0237] The secondary battery was prepared in the same manner as in Comparative Example 2, except that the silicon-based active material prepared in Example 6 was Si / C instead of pure Si powder.

[0238] The prepared negative electrode active material exhibited an average particle size (D50) of 8.2 μm and formed a coating with an average thickness of 70 nm non-uniformly. Subsequently, a secondary battery was prepared in the same manner as in Example 6. That is, Comparative Example 5 used a negative electrode active material with a coating that did not contain an aqueous binder.

[0239] <Comparative Example 6>

[0240] The secondary battery was prepared in the same manner as in Comparative Example 3, except that the silicon-based active material was Si / C prepared in Example 6 instead of pure Si powder.

[0241] The prepared negative electrode active material exhibits an average particle size (D50) of 8.1 μm, and the coating is almost invisible on the surface of the silicon-based active material, so the thickness of the coating cannot be measured.

[0242] Experimental Example 1: Evaluation of Capacity Retention

[0243] The lifetime and capacity retention of the secondary batteries prepared in the Examples and Comparative Examples were evaluated using electrochemical charge / discharge tests. In-situ cycling tests were performed on the secondary batteries under 1C charge and 1C discharge conditions within a voltage range of 4.2–2.5V. The tests were terminated in the discharged state after 200 cycles. Additionally, every 50 cycles, charge / discharge was performed at 0.33C / 0.33C within a voltage range of 4.2–2.5V to measure capacity retention; the results are shown in Tables 1 and 2.

[0244] Capacity retention (%) = {(Discharge capacity in the Nth cycle) / (Discharge capacity in the first cycle)} x 100%

[0245] Experimental Example 2: Evaluation of the Aqueous Processability of Slurry

[0246] The aqueous processability of the negative electrode slurries prepared in the examples and comparative examples was evaluated by placing each negative electrode slurry in a single cell case and measuring the changes in gas production after high-temperature storage.

[0247] For example, each negative electrode slurry was placed in a single cell casing and stored in a constant temperature chamber at 60°C for 3 days. After 3 days of storage, the volume deviation before and after storage was measured. Based on Archimedes' principle, the volume of gas generated was calculated by converting the mass difference measured from the negative electrode slurry into volume, and the amount of gas generated is shown in Tables 1 and 2.

[0248] Gas production (%) = {(Volume after storage - Volume before storage) / (Volume before storage)} × 100%

[0249] [Table 1]

[0250] Referring to Table 1, Examples 1 to 5, which contain silicon-based anode active materials according to one embodiment of this disclosure, exhibit a capacity retention of approximately 62% to 68% and a gas generation of 0%. In contrast, Comparative Examples 1 to 3 exhibit a capacity retention of approximately 58% to 61% and a gas generation of 6.7% to 8.9%. Therefore, it can be confirmed that Examples 1 to 5 exhibit superior capacity retention and gas generation characteristics compared to Comparative Examples 1 to 3.

[0251] [Table 2]

[0252] Referring to Table 2, Examples 6 to 9, which contain a negative electrode active material according to one embodiment of the present disclosure, exhibit a capacity retention rate of approximately 96.8% to 99.1% and a gas generation rate of 0%. In contrast, Comparative Examples 4 to 6 show a capacity retention rate of approximately 95.5% to 96.1% and a gas generation rate of 12% to 23%. Therefore, it can be confirmed that Examples 6 to 9 exhibit superior capacity retention and gas generation characteristics compared to Comparative Examples 4 to 6.

[0253] Referring to Tables 1 and 2, in Comparative Examples 1 and 4, which used silicon-based active materials that did not undergo a separate coating formation process, poor capacity retention and gas generation were observed. For example, in terms of gas generation, the amount of gas generated in Comparative Example 1 was relatively high compared to Comparative Examples 2 and 3, and the amount of gas generated in Comparative Example 4 was also relatively high compared to Comparative Examples 5 and 6. This result is understood to be due to the direct contact between the silicon-based active material and the aqueous solvent, which causes a large amount of gas (e.g., H2 gas) to be generated in the slurry during the aqueous process.

[0254] In Comparative Examples 2 and 5, silicon-based active materials coated only with metal oxides were used. Because the coating did not contain a water-based binder, an uneven coating was formed on the surface of the silicon-based active material. Furthermore, in Comparative Examples 3 and 6, silicon-based active materials coated only with water-based binders were used. Because the coating did not contain metal oxides, almost no coating was formed on the surface of the silicon-based active material, and the coating thickness could not be measured. Therefore, in Comparative Examples 2, 3, 5, and 6, the coating did not adequately function as a resist layer, resulting in poor capacity retention, and the insufficient coating caused excessive gas generation during the water-based process.

[0255] In Examples 1 to 3, it was confirmed that excellent capacity retention was observed even compared to Examples 4 and 5. Furthermore, in Examples 6 to 8, it was confirmed that excellent capacity retention was observed even compared to Example 9. This confirms that when the content of metal oxides and aqueous binders in the coating is adjusted to optimal levels, a uniform coating is formed on the surface of the silicon-based active material. In Example 4, it was understood that the relatively low content of metal oxides in the coating resulted in the coating not adequately functioning as a resistance layer. Furthermore, in Examples 5 and 9, it was understood that the relatively low content of aqueous binders in the coating reduced the coating's flexibility, leading to particle breakage due to volume changes during charge and discharge, thus reducing capacity retention due to the generation of byproducts.

[0256] Although the technology of this disclosure has been described with reference to embodiments, those skilled in the art will understand that various modifications and changes can be made to the various embodiments of this disclosure without departing from the technical scope of the various embodiments of this disclosure as defined in the appended claims. Therefore, the technical scope of the various embodiments of this disclosure is not limited to the detailed description of the invention herein, but should be determined by the scope defined in the claims.

Claims

1. A negative electrode active material, said negative electrode active material comprising: Silicon-based active materials; and A coating disposed on the silicon-based active material The coating comprises a metal oxide and a water-based binder.

2. The negative electrode active material according to claim 1, wherein the silicon-based active material comprises at least one selected from Si, SiO x (0<x<2), Si / C, and Si alloys.

3. The negative electrode active material according to claim 2, wherein the silicon-based active material comprises Si, and Based on 100 parts by weight of the silicon-based active material, the content of Si is 70 parts by weight or more.

4. The negative electrode active material according to claim 1, wherein the silicon-based active material comprises Si / C.

5. The negative electrode active material according to claim 4, wherein the Si / C comprises porous carbon and silicon deposited on the porous carbon.

6. The negative electrode active material according to claim 1, wherein the metal oxide is represented by Formula 1: [Formula 1] M a O b (1≤a≤2, 1≤b≤5) M can be any one of Al, Ti, and Mg.

7. The negative electrode active material according to claim 1, wherein the metal oxide comprises at least one selected from Al2O3, TiO2 and MgO.

8. The negative electrode active material according to claim 1, wherein the aqueous binder comprises at least one selected from the group consisting of polyacrylamide (PAM), polyacrylic acid (PAA), polyvinyl alcohol (PVA), polyethylene glycol (PEG), carboxymethyl cellulose (CMC), polyvinyl acetate (PVAc), polyvinylpyrrolidone (PVP), and substances thereof in which hydrogen is replaced by Li, Na or Ca.

9. The negative electrode active material according to claim 1, wherein the coating comprises the metal oxide and the aqueous binder in a weight ratio of 70:30 to 90:

10.

10. The negative electrode active material according to claim 1, wherein the average particle size (D50) of the negative electrode active material is from 1 μm to 20 μm.

11. The negative electrode active material according to claim 1, wherein the average thickness of the coating is from 100 nm to 1 μm.

12. A negative electrode composition comprising a negative electrode active material according to any one of claims 1 to 11.

13. The negative electrode composition according to claim 12, wherein the negative electrode active material further comprises a carbon-based active material.

14. The negative electrode composition according to claim 13, wherein the carbon-based active material comprises at least one selected from natural graphite and artificial graphite.

15. The negative electrode composition according to claim 13, wherein the content of the carbon-based active material is 70 parts by weight or more based on 100 parts by weight of the negative electrode active material.

16. The negative electrode composition according to claim 12, wherein the negative electrode composition further comprises: Negative electrode adhesive, The negative electrode adhesive comprises a water-based adhesive.

17. A negative electrode, said negative electrode comprising: Negative current collector layer; and A layer of negative electrode active material disposed on one or both surfaces of the negative electrode current collector layer. The negative electrode active material layer comprises the negative electrode composition according to claim 12.

18. A secondary battery, the secondary battery comprising: Positive electrode; and The negative electrode according to claim 17.

19. A battery module comprising a secondary battery according to claim 18.

20. A battery pack comprising a secondary battery according to claim 18.

Citation Information

Patent Citations

  • Anode for lithium ion battery

    JP2009080971A

  • User program exception error maintenance method of PLC system

    KR1020240145317A